Metformin-induced suppression of IFN-α via mTORC1 signalling following seasonal vaccination is associated with impaired antibody responses in type 2 diabetes - Saenwongsa, Wipawee; Nithichanon, Arnone; Chittaganpitch, Malinee; Buayai, Kampaew; Kewcharoenwong, Chidchamai; Thumrongwilainet, Boonyarat; Butta, Patcharavadee; Palaga, Tanapat; Takahashi, Yoshimasa; Ato, Manabu; Lertmemongkolchai, Ganjana (Scientific reports, 2020)
Diabetes mellitus (DM) patients are at an increased risk of complications following influenza-virus infection, seasonal vaccination (SV) is recommended. However, SV with trivalent influenza vaccine (TIV) can induce antibody and type-I interferon (IFN) responses, and the effect of anti-DM treatment on these responses is incompletely understood. We evaluated the antibody response and IFN-α expression in individuals with and without type 2 DM (T2DM) following SV, and examined the effects on anti-DM treatment. TIV elicited sero-protection in all groups, but antibody persistency was < 8 months, except for the antibody response to B-antigens in non-DM. T2DM impaired the IgG avidity index, and T2DM showed a significantly decreased response against H1N1 and H3N2, in addition to delaying and reducing haemagglutination-inhibition persistency against influenza B-antigens in DM groups treated with metformin (Met-DM) or glibenclamide (GB-DM). Following TIV, the Met-DM and GB-DM groups exhibited reduced IFN-α expression upon stimulation with whole- and split-virion influenza vaccines. Suppression of IFN-α expression in the Met-DM group was associated with a reduction in the mechanistic target of rapamycin complex-1 pathway and impaired IgG avidity index. Thus, single-dose TIV each year might not be suitable for T2DM. Our data could aid the development of an efficacious influenza vaccine for T2DM.